Relative control of an ion beam shepherd satellite using the impulse compensation thruster. (October 2018) - Alpatov, A.; Khoroshylov, S.; Bombardelli, C.
Abstract: The "ion beam shepherd" is a recently proposed concept for removing space debris in a contactless manner. A shepherd satellite must be controlled to move at a certain small distance in front of a space debris object during the de-orbiting phase. Because of the considerable duration of this phase, the propellant consumption is a key requirement for the control design. In this paper, the in-plane relative position of the shepherd is maintained using a small thrust variation of the compensation thruster. The controller is designed and analyzed considering the time-varying and parametric uncertain plant in the presence of the ion beam and orbital perturbations, sensor noise, actuation errors, taking into account limitations on the controller output. The system robustness and specified requirements are confirmed both by a formal criteria and numerical simulations. The estimations show that this control strategy is more efficient in terms of propellant consumption than the conventional approach with chemical thrusters. Highlights: The in-plane position of the shepherd satellite is maintained using only one thruster. The system robustness and specified requirements are validated. The control strategy is efficient in terms of propellant consumption.